Synthesis, Molecular Docking, and DFT Studies of Some New 2, 5-Disubstituted Benzoxazoles as Potential Antimicrobial and Cytotoxic Agents. (21st April 2022) - Erol, Meryem; Celik, Ismail; Uzunhisarcikli, Ebru; Kuyucuklu, Gulcan
Abstract: In this study, a total of 17 piece 2, 5-disubstituted benzoxazole derivatives were synthesized, 2 of which were not original, their antimicrobial activities were determined using microdilution method and their in vitro cytotoxic activities were investigated on MCF-7 and A549 cells by MTT test. When the activity results are examined, although the antibacterial effects of benzoxazole derivatives are weaker than standard drugs; 3N13 and 3N19 against Candida albicans isolate showed the closest activity to fluconazole with MIC: 16 µg/ml. The cytotoxicity test was measured at a concentration of 100 µM and a 24-h incubation period. The results showed that the compounds had weak activities against two cell lines. Molecular docking studies of synthesized compounds were performed on sterol 14α-demethylase protein (CYP51) and protein-ligand interactions of 3N13, the most effective derivative against C. albicans isolate, were showed (PDB: 5TZ1). Estimated ADME profiles of compounds were calculated and also 3N13 's were calculated HUMO-LUMO energies, molecular electrostatic potential analysis, and geometric optimization parameters with 6-311 G+ (d, p) base set using DFT/B3LYP theory, and the results were displayed.